Overview of Malaria Incidents Based on Secondary Data in Kaimana Regency, Papua: 2014-2017 - Wahyuni, Ade Sri; Dwiyanti, Selfin (Journal of Epidemiology and Health Science, 2026)
Background: Malaria, a disease caused by the Plasmodium parasite and transmitted trough the bite of the Anopheles mosquito, remains a global  and Indonesia health. Although the national morbidity rate tends to decrease, several regions, especially in eastern Indonesia, still experience high incidence rates. Kaimana Regency is one area significantly impacted. This study aims to provide an overview of malaria incidence trends in Kaimana regency based on availablle secondary data. Objective: To describe the trends and characteristics of malaria incidence in Kaimana regency based on secondary data from the Kaimana regency Health Office. Method:  This Quantitative descriptive studi uses secondary data from the  Kaimana regency Health Office. Data were analyzed descriptively using tables and graphs Results: Analysis of secondary data show fluctuations in malaria incidence rates. Although there was a temporary decrease  2016, there was a significant increase in 2017. Conclusion: Fluctuations in malaria cases in Kaimana  Regency 2014-2017, with an alarming increase in 2017. highlight the need for more effective interventions to prevent and control malaria in the region. Further research is needed to identify the factors contributing to these fluctuations and to develop more targeted control. Keywords: Malaria, Anopheles, Plasmodium, Kaimana Regency, Papua Barat, Indonesia